International Transfer Pricing in Asia Pacific Perspectives on Trade between Australia, New Zealand and China - Li, Jian; Paisey, Alan (Palgrave Macmillan UK, 2005)
In the management of business activity by companies operating in more than one country, the complex array of issues and practices that characterize their movements of assets between constituent company units centres around what has become known as international transfer payments. This book, based on extensive research, explains the nature of the subject, presents the latest data on the practice of transfer payments in three Asia Pacific countries; the regulations, attitudes and conditions which form the context in which they take place; and the events which are most likely to precipitate the intervention of the authorities and lead to investigation and audit
Keywords: Business; Ethnology / Asia; Business enterprises / Finance; Finance; Corporations / Finance; International economics